DUKUNGAN YANG TERIMA PADA PRIMIPARA SAAT DIPUTUSKAN SECTIO CAESAREA DARURAT - Febria Syafyu Sari (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Primipara who will undergo childbirth by caesarea sectio (CS) require social assistance. Theabsence of social support led to primipara in the preoperative SC may increase the risk ofpostpartum depression and moderate anxiety. Qualitative research with descriptivephenomenology design approach aimed at exploring primipara support at the time decided byemergency caesarea sectio (CS). The study was conducted in January - July 2016 in Midwiferyroom, with six participants, six emergency CS patients. The results of this study were analyzedusing Collaizi method. Ethics considered in this study with respect to the principles of researchethics and the validity of data pay attention to the criteria: credibility, transferability,dependability and confirmability. The result of research is social support received by primiparaare husband, family and health officer. The results of this study can be concluded that thesupport of husbands, families and health workers is a person who is also trusted by theparticipants and become one source of support so that support will be very useful. Suggestionsfor mothers can be the next lesson in dealing with labor by looking at experience in facingpreoperative emergency CS.Keywords: Ceasarea Sectio, Primipara, Support